Efficacy of heparin in respiratory support of near-term rabbits with meconium-induced acute lung injury: Linear regression model analyses - Siyu Xie; Qiang Gu; Guiyin Zhuang; Xiaojing Guo; Bo Sun (PLoS ONE, 2026)
Objectives To explore the pharmacotherapeutic efficacy of heparin in the management of meconium-induced acute lung injury (ALI) in near-term newborn rabbits subjected to mechanical ventilation (MV) and ancillary respiratory medications. Methods Newborn rabbits at 30-day gestation (term 31 days) were anesthetized, intratracheally intubated and received human meconium-saline suspension, followed by parallel MV with individually adjusted tidal volume in a multi-plethysmograph-ventilator system. When ALI was induced after initial 3-h MV, therapeutic effects of single or combined subcutaneous heparin (100 U/kg), surfactant (200 mg/kg), and inhaled nitric oxide (iNO, 10 ppm), were compared for lung protective ventilation and survival as outcome, analyzed with linear regression models. Results Significantly reduced respiratory compliance by meconium was reinstalled during ensuing 7-h MV, with improved survival, among the treatment groups. The impact was verified by lung injury severity, surfactant phospholipid pools, and multiple mRNA expressions of surfactant proteins, lung fluid clearance-related factors, inflammatory mediators, growth factors, endothelial cell injury and coagulation-related factors as subphenotyping biomarkers. The overall benefits of heparin alone, or exerted with the dual and triple regimens, were discernible by both generalized linear model and Cox proportional hazard ratio regression for survival and other major variables as outcome. Its adverse effects were intangible. Conclusion The comparable efficacy of heparin, alongside the PS and NO, was corroborated in attenuating meconium-mediated, ventilator-induced ALI, which should warrant clinical investigation to validate.